Multilingualism Codes Reflected On Efl Students’ Social Media Posts - Nur Sayima Mantadji, Raifida; Dg. Macora, Yuliana (Sintuwu Maroso Journal of English Teaching, 2023)
The research intends to figure out the language, types and levels of code mixing used in social media posts of the students majoring in English at UniverstasSintuwuMaroso. The research applies qualitative method to get thelanguage, types and level of Code-Mixing, while the analysis uses Maher’s (1995), Hoffman's (1991) and Suwito's (1988) theories. The results show that out of 46 students, only 9 used code mixing in their captions of social media posts with 33 posts. The students’ of English Language Education Study Program are able to practice multilingualism because they can usecode mixing by combining Bahasa, English, and Arabicin their captions of social media. Intra-sentential type of code mixing is more dominant because there are 29 data, 1 data of Intra-lexical type, and 3 data of involving a change of pronunciation type. While at the level of code-mixing, the word level is more dominant because there are 19 data, the phrase level is 13 data, then the clause level is 3 data, the baster level is 1 data and there are no data found of the repetition word, and idiom level.